Ag nanoparticle-blended plasmonic organic solar cells : performance enhancement or detraction? - Wu, Bo (2014)
The blending of metallic nanoparticles into the active layer of organic solar cells in a bid to enhance their light absorption and device performance has led to controversial reports of both efficiency enhancement and degradation. Herein, through comprehensive transient absorption spectroscopy, we present clear evidence of traps being responsible for performance degradation of poly (3-hexylthiophene): [6,6]-phenyl-C 61-butyric acid methyl ester organic photovoltaic devices incorporated with oleylamine-capped silver nanoparticles. Although the presence of the metallic nanoparticles leads to more excitons being generated in the active layer, higher losses suffered by the polaron population through trap-assisted recombination strongly limits the device performance. Device modeling based on a single mid-gap trap state introduced by the AgNPs can well reproduce the current-voltage curves of the plasmonic organic solar cells – in agreement with the transient absorption findings. These new insights into the photophysics and charge dynamics of plasmonic organic solar cells would help resolve the existing controversy and provide clear guidelines for device design and fabrication.